Impact des menstruations sur les gains de force : une étude portant sur 12 semaines - Holland-Coulton, I.; Tallent, J.; Price, P.; Cushion, E. J. (Science & Sports, 2025)
Objectives Determine if the number of days in menses affects back squat strength gains and to assess the feasibility of using autoregulation in resistance training. Equipment and methods Nineteen (n = 19) eumenorrheic, recreationally trained female subjects (age: 32 ± 3.78 years, body mass 64.68 ± 6.18 kg, height 167.79 ± 6.02 cm) participated in three resistance training sessions per week over 12 weeks. Sets and repetitions were fixed, with subjects adjusting intensity using repetitions in reserve (RIR). Pre- and post-1-repetition maximum strength tests (1RM) measured back squat strength gains. Subjective measures were taken via the Borg's Rate of Perceived Exertion scale (RPE) and the Total Quality Recovery questionnaire (TQR). Menstrual cycle (MC) data was collected from subjects via the FitrWoman app. Results Participants recorded 100% of the required data and completed all prescribed training sessions. A significant increase in mean back squat strength was observed (n = 19, P < 0.001, d = 0.67). Performance data showed no significant differences between fewer or more days in menses for back squat tests, total training volume load, and TQR results. There were significant increases in session RPE for subjects with more days in menses (F [10, 170] = 2.175, P = 0.021, np2 = 0.113). There was no significant increase in body mass over the 12 weeks. Conclusion The study demonstrates that days in menses do not significantly affect training outcomes, but a higher perceived exertion was reported for those with more days in menses. Furthermore, the research demonstrates autoregulation is a feasible approach for training female athletes.